Molecular and Morphological Differentiation of Common Dolphins (Delphinus sp.) in the Southwestern Atlantic: Testing the Two Species Hypothesis in Sympatry - Cunha, Haydeé A. (2015)
The taxonomy of common dolphins (Delphinus sp.) has always been controversial, with over twenty described species since the original description of the type species of the genus (Delphinus delphis Linnaeus, 1758). Two species and four subspecies are currently accepted, but recent molecular data have challenged this view. In this study we investigated the molecular taxonomy of common dolphins through analyses of cytochrome b sequences of 297 individuals from most of their distribution. We included 37 novel sequences from the Southwestern Atlantic Ocean, a region where the short- and long-beaked morphotypesoccur in sympatry, but which had not been well sampled before. Skulls of individuals from the Southwestern Atlantic were measured to test the validity of the rostral index as a diagnostic character and confirmed the presence of the two morphotypes in our genetic sample. Our genetic results show that all common dolphins in the Atlantic Ocean belong to a single species, Delphinus delphis. According to genetic data, the species Delphinus capensis is invalid. Long-beaked common dolphins from the Northeastern Pacific Ocean may constitutea different species. Our conclusions prompt the need for revision of currently accepted common dolphin species and subspecies and of Delphinus delphis distribution.